Interleukin-20 targets renal mesangial cells and is associated with lupus nephritis - Li, Hsing-Hui (Clinical immunology (Orlando, Fla.), 2008)
Lupus nephritis is one manifestation of systemic lupus erythematosus (SLE). Interleukin (IL)-10 is involved in the pathogenesis of SLE. To determine whether IL-20, a member of the IL-10 family, is associated with lupus nephritis, we analyzed the expression of IL-20 and its receptors in mesangial cells derived from SLE-prone, NZB/W, and DBA/W mice. IL-20 and its receptors were upregulated in mesangial cells from NZB/W mice. Incubating IL-20 with mesangial cells upregulated the transcripts of CCL2 (MCP-1), CCL5 (RANTES), CXCL10 (IP-10), IL-6, iNOS, and ROS, all of which are involved in the pathogenesis of lupus nephritis. IL-20 specifically activated the downstream signal ERK 1/2. We also detected human IL-20 protein in both mesangial cells and inflammatory cells in kidney biopsies of patients with lupus nephritis. Our results reveal the novel effects of IL-20 on mesangial cells and its association with lupus nephritis